Salmon lice evasion, susceptibility, retention, and development differ amongst host salmonid species. (12th December 2017) - Bui, Samantha; Halttunen, Elina; Mohn, Agnes M; Vågseth, Tone; Oppedal, Frode
Abstract: With different ecological characteristics amongst salmonid species, their response to parasitic infestation is likely to vary according to their spatial and temporal overlap with the parasite. This study investigated the host–parasite interactions amongst three species of salmonids and the ectoparasitic salmon louse, Lepeophtheirus salmonis . To determine any variation in infestation parameters amongst salmonids, single population groups of Atlantic salmon ( Salmo salar ), chinook salmon ( Onchorhynchus tshawytscha ), and previously-infested and naïve sea trout ( Salmo trutta ) were exposed to a controlled infestation challenge. We found that chinook salmon and both sea trout groups were more susceptible to acquiring lice than Atlantic salmon. Behavioural responses during infestation were more pronounced in Atlantic and chinook salmon. Parasite development was similar in lice attached to Atlantic salmon and sea trout, but hindered on chinook salmon. At 16 days post-infestation, chinook salmon had reduced lice loads to the same level as Atlantic salmon, whilst sea trout retained their lice. These results demonstrate differences in interactions with L. salmonis amongst these species, and highlight the vulnerability of sea trout to infestation.